Sistematik Review: Meta-Analisis Beban Kerja Karyawan dan Upaya Penanggulangannya - Fajar Okta Widarta; Riza Ulhaq; Gaustama Putra; Khairul Hadi (Jurnal Optimalisasi, 2026)
Employee productivity and workload are closely correlated. Employees are frequently physically and psychologically burdened by high goals and unfavorable working conditions. Industry participants and business actors must be aware of these problems and the steps that can be taken to solve them. In order to help business actors and industry participants solve connected issues, this study attempts to compile a variety of research findings on employees' physical and mental pressures and attempts to overcome them. The Publish or Perish 8 program was used to collect data via meta-analysis. The Google Scholar database was used to compile articles published between 2022 and 2024. Data collecting, data reduction, data presentation, and conclusion-drawing were the phases of the meta-analysis that produced 34 papers. According to the survey, employees' mental workload problems were more common than their physical workload. The issue of employee workload can be resolved by routinely assessing employee workloads to ascertain when hiring more personnel is required, upholding a safe and comfortable workplace, allocating workloads equitably, supplying sufficient personal protective equipment, and paying all employees appropriately